Diamond detectors for hadron physics research - Berdermann, Elèni; Pomorski, Michał; Boer, Wim de; Ciobanu, Mircea; Dunst, S.; Grah, Christian; Kis, Milos; Koenig, W.; Lange, W.; Lohmann, Wolfgang; Lovrinčić, Robert; Moritz, P.; et al. (Diamond and related materials, 2010)
The application of diamond for the detection of charged particles in atomic, nuclear and high-energy physics experiments is described. We compare the properties of three undoped diamond types, all of them produced by Chemical Vapor Deposition (CVD), in particular homoepitaxial single-crystal CVD Diamond (scCVDD), polycrystalline CVD Diamond (pcCVDD) grown on silicon, and CVD Diamond on Iridium (DoI) grown on the multi-layer substrate Ir/YSZ/Si001. The characteristics of the transient current (TC) signals generated from 241Am-α-particles in the samples are exploited to evaluate the potential of the diamond crystals for particle timing and spectroscopy applications. The TC technique (TCT) results are correlated to the dark conductivity and the structural defects of the bulk materials as well as to the morphology and roughness of the diamond surfaces. The deterioration of the sensors performance after heavy irradiations with 26 MeV protons, 20 MeV neutrons, and 10 MeV electrons is discussed by means of charge-collection efficiency results, TC technique, and optical absorption spectroscopy (OAS). The important role of the diamond signal processing is underlined, which influences both the quality of the CVDD characterization data as well as the in-beam performance of the diamond sensors.
Available online 8 December 2009
Gesehen am 17.01.2023